Quorum sensing regulation confronts the development of a viable but non‐culturable state in Vibrio cholerae. (6th May 2020) - Wu, Bin; Liang, Weili; Yan, Meiying; Li, Jie; Zhao, Hongqun; Cui, Lunbiao; Zhu, Fengcai; Zhu, Jun; Kan, Biao
Summary: Vibrio cholerae can enter a viable but non‐culturable (VBNC) state when it encounters unfavourable environments; VBNC cells serve as important reservoirs and still pose threats to public health. The genetic regulation of V. cholerae entering its VBNC state is not well understood. Here, we show a confrontation strategy adapted by V. cholerae O1 in which it utilizes a quorum sensing (QS) system to prevent transition into a VBNC state under low nutrition and temperature conditions. The upregulation of hapR resulted in a prolonged culturable state of V. cholerae in artificial sea water at 4°C, whereas the mutation of hapR led to fast entry into the VBNC state. We also observed that different V. cholerae O1 natural isolates with distinct QS functions present a variety of abilities to maintain culturability during the transition to a VBNC state. The strain groups with higher or constitutive expression of QS genes exhibit a greater tendency to maintain the culturable state during VBNC induction than those lacking QS functional groups. In summary, HapR‐mediated QS regulation is associated with the transition to the VBNC state in V. cholerae . HapR expression causes V. cholerae to resist VBNC induction and become dominant over competitors in changing environments.